CAN ALLIANCE WITH THE POORS BUILD SUSTAINABLE COMPETITIVE ADVANTAGE IN AGRICULTURAL BASED INDUSTRY? - Ina A. Murwani (Journal of Business Strategy and Execution, 2015)
The sustainability of business that involves the participation of the poor into the strategy is always intriguing in the perspective of the process and feasibility.This paper try to analyze a firm that embeds corporate social responsibility strategy as part of their business rather the reputation as a benchmark to create argumentationthat support the proposition that alliance with the poors can build sustainable competitive advantage. The theory of Industrial Organization, Resource Based View, Network and Stakeholder theory is used as the tool to draw the conclusion.